Training of Specialists in the Field of Electronic Marketing: Staff for the Digital Economy of the Republic of Belarus - L. I. Arhipova; E. N. Zhivitskaya; L. P. Knyazeva; I. V. Marakhina; V. A. Parhimenko (Цифровая трансформация)
The tendencies of development of marketing in conditions of digital transformation of economy are considered in the article. The concept of electronic marketing is presented. The condition of training of specialists in the field of electronic marketing in the Republic of Belarus is described. The necessity of training of specialists in the field of e-marketing on the second stage of higher education is substantiated. The special features of this field of study are distinguished in comparison with the baccalaureate and in comparison with related directions of the master's programm.